Value of internal limiting membrane peeling in surgery for idiopathic macular hole stage 2 and 3: a randomised clinical trial. Issue 8 (21st November 2008) - Christensen, U C; Krøyer, K; Sander, B; Larsen, M; Henning, V; Villumsen, J; la Cour, M
Abstract : Aim: To determine the effect of internal limiting membrane (ILM) peeling on anatomical and functional success rates in stage 2 and 3 idiopathic macular hole surgery (MHS). Methods: Randomised clinical trial of stage 2 and 3 idiopathic macular hole without visible epiretinal fibrosis and with less than 1 year's duration of symptoms. Eyes were randomised to (1) vitrectomy alone without retinal surface manipulation, (2) vitrectomy plus 0.05% isotonic Indocyanine Green (ICG)-assisted ILM peeling or (3) vitrectomy plus 0.15% Trypan Blue (TB)-assisted ILM peeling. Main outcomes were hole closure after 3 and 12 months and best-corrected visual acuity after 12 months. Results: 78 eyes were enrolled. Primary closure rates were significantly higher with ILM peeling than without peeling for both stage 2 holes (ICG peeling 100%, non-peeling 55%, p = 0.014) and for stage 3 holes (ICG peeling 91%, TB peeling 89%, non-peeling 36%, p<0.001). Visual outcomes in eyes with primary hole closure were not significantly different between the groups. Conclusions: Dye-assisted ILM peeling was associated with significantly higher closure rates than non-peeling in both stage 2 and 3 MHS. Intraoperative ILM staining with 0.05% isotonic ICG was not associated with a significantly different visual outcome than non-peeling or TB peeling in eyes with primary hole closure. Trial registration number: NCT00302328.